2023
DOI: 10.1021/acs.orglett.3c01033
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Electrochemical Carboxylation of Naphthalene with CO2: Selective Monocarboxylation of 2-Substituted Naphthalenes

Abstract: Numerous remarkable reactions based on electrochemical carboxylations using CO2 have recently attracted considerable attention. In contrast to more recent examples, the electrochemical carboxylation of naphthalene had already been established in 1959, whereby a dearomative dicarboxylation selectively produces 1,4-dicarboxylated 1,4-dihydronaphthalene derivatives. Here, we report that the use of electron-deficient naphthalene derivatives in the presence of a redox mediator such as p-terphenyl and H2O under CO2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…In a later study, they found that addition of 1 equivalent of water is also beneficial for the dearomatizing monocarboxylation of electron-deficient naphthalenes with FEs up to 57% for 1,2-dihydronaphthalene derivatives. 134…”
Section: Carboxylationsmentioning
confidence: 99%
“…In a later study, they found that addition of 1 equivalent of water is also beneficial for the dearomatizing monocarboxylation of electron-deficient naphthalenes with FEs up to 57% for 1,2-dihydronaphthalene derivatives. 134…”
Section: Carboxylationsmentioning
confidence: 99%
“…The subsequent reaction of A with CO 2 results in carboxylate intermediate C , stabilized with a zinc counter-ion. 21,37 The C 14 H 10 -mediated reduction of intermediate C then gives anion D , 38 which protonation leads to salt E . The target carboxylic acid 2 is obtained during acid work-up.…”
mentioning
confidence: 99%
“…We envisioned that, upon the electrophilic nature of CO 2 , the radical-mediated carboxylation of propargylic alcohols for the synthesis of tetrasubstituted 2,3-allenoates could be achieved by utilizing a suitable reductive condition to generate the CO 2 radical anion intermediate or the propargylic alcohol radical anion intermediate . Herein, we report the first example of electroreductive carboxylation of propargylic alcohols with CO 2 and then a simple workup with TMSCHN 2 to provide tetrasubstituted 2,3-allenoates (Scheme d).…”
mentioning
confidence: 99%
“…The plausible mechanism for this electroreductive carboxylation protocol was proposed on the basis of the current results and precedent literature (Scheme ). , Initially, CO 2 underwent cathodic reduction to produce the CO 2 radical anion intermediate A . , With the aid of Mg 2+ (Figure S8), which is generated from the magnesium flake anode, the intermediate A is converted to the MOOC· radical intermediate B . Radical addition of intermediate B across the CC bond of propargylic acetate 1 generates alkenyl radical intermediate C , followed by single electron transfer (SET) with the CO 2 radical anion intermediate A to deliver alkenyl anion intermediate D .…”
mentioning
confidence: 99%